Physiological Response to Salinity and Alkalinity of Rice Genotypes of Varying Salt Tolerance Grown in Field Lysimeters - Surekha Rao, P. (Journal of Stress Physiology & Biochemistry, 2013)
Soil salinity and alkalinity seriously threaten rice production in south Asia. Improving screening methodologies to identify sources of tolerance for improved breeding for salt tolerant rice is of continuing importance. Rice genotypes of varying salt tolerance, such as tolerant (T), semi-tolerant (ST), and sensitive (S), were grown in field lysimeters in saline soil of ECe 4 and 8 mS cm-1 and alkali soil of pH 9.5 and 9.8 in North India and analyzed for chlorophyll (Chl), sugar, starch and proline in leaves. Chlorophyll a and b decreased due to salinity in all the tolerance groups. However, Chl a was not much affected but chl b increased with alkalinity. Under high stress both at ECe 8 and pH 9.8 Chl a and b were more in tolerant than in sensitive genotypes. The ratio of Chl a/b was similar in T, ST and S genotypes under salinity stress. Sugar accumulation was higher in T compared to S under normal conditions but under salinity or alkalinity stress the differences were not significant. Leaf starch was highest in T, intermediate in ST and lowest in S genotypes in normal as well as under salinity and alkalinity stress. There was decrease in starch with salinity and alkalinity stress only in T group but not in ST and S group. Proline increased significantly in all the tolerance groups even at low salinity of ECe 4 mS cm -1 or pH 9.5. The salt tolerant genotypes of rice maintained higher levels of Chl a and b, starch and proline under high salinity and alkalinity stress and are the robust criteria for tolerating high salinity and alkalinity.